A computational study on the electronics and transport properties of ultranarrow graphene nanoconstriction [electronic resource] - Sakina Shamim Husain, 1992- (Johor Bharu : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2015